Recommendations for the management of COVID-19 in patients with haematological malignancies or haematopoietic cell transplantation, from the 2021 European Conference on Infections in Leukaemia (ECIL 9) - Cesaro, Simone; Ljungman, Per; Mikulska, Malgorzata; Hirsch, Hans H.; Von Lilienfeld-Toal, Marie; Cordonnier, Catherine; Meylan, Sylvain; Mehra, Varun; Styczynski, Jan; Marchesi, Francesco; Besson, Caroline; Baldanti, Fausto; et al. (Leukemia, 2022)
Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) is a novel virus that spread worldwide from 2019 causing the Coronavirus disease 19 (COVID-19) pandemic. SARS-CoV-2 infection is characterised by an initial viral phase followed in some patients by a severe inflammatory phase. Importantly, immunocompromised patients may have a prolonged viral phase, shedding infectious viral particles for months, and absent or dysfunctional inflammatory phase. Among haematological patients, COVID-19 has been associated with high mortality rate in acute leukaemia, high risk-myelodysplastic syndromes, and after haematopoietic cell transplant and chimeric-antigen-receptor-T therapies. The clinical symptoms and signs were similar to that reported for the overall population, but the severity and outcome were worse. The deferral of immunodepleting cellular therapy treatments is recommended for SARS-CoV-2 positive patient, while in the other at-risk cases, the haematological treatment decisions must be weighed between individual risks and benefits. The gold standard for the diagnosis is the detection of viral RNA by nucleic acid testing on nasopharyngeal-swabbed sample, which provides high sensitivity and specificity; while rapid antigen tests have a lower sensitivity, especially in asymptomatic patients. The prevention of SARS-CoV-2 infection is based on strict infection control measures recommended for aerosol-droplet-and-contact transmission. Vaccinations against SARS-CoV-2 has shown high efficacy in reducing community transmission, hospitalisation and deaths due to severe COVID-19 disease in the general population, but immunosuppressed/haematology patients may have lower sero-responsiveness to vaccinations. Moreover, the recent emergence of new variants may require vaccine modifications and strategies to improve efficacy in these vulnerable patients. Beyond supportive care, the specific treatment is directed at viral replication control (antivirals, anti-spike monoclonal antibodies) and, in patients who need it, to the control of inflammation (dexamethasone, anti-Il-6 agents, and others). However, the benefit of all these various prophylactic and therapeutic treatments in haematology patients deserves further studies.
CRIS-Team Scopus Importer:2023-03-23